BIOETHICAL CULTURE AS A FOUNDATION FOR RESPONSIBLE HUMAN DEVELOPMENT IN THE CONTEMPORARY WORLD (Eureka Journal of Humanities and Social Research, 2026)
The rapid development of science, biotechnology, medicine, and digital technologies has significantly expanded human capabilities while simultaneously generating new ethical challenges. Under these conditions, bioethical culture has become an essential component of social development, ensuring a balance between scientific progress and human values. This article examines the theoretical foundations, social significance, and practical implications of bioethical culture in contemporary society. The study analyzes the role of bioethical principles in shaping responsible behavior, protecting human dignity, and promoting sustainable development. Using analytical and comparative research methods, the article explores the relationship between bioethical awareness and social responsibility. The findings demonstrate that the formation of bioethical culture contributes to the development of ethical decision-making, respect for human rights, environmental responsibility, and the effective regulation of scientific innovations.
Keywords: Bioethics, bioethical culture, human dignity, social responsibility, biotechnology, sustainable development, ethical values, healthcare ethics.